KEPUASAN KERJA PEGAWAI SEKSI PENDATAAN DAN PENETAPAN PAJAK DALAM PELAYANAN PUBLIK - Candani, Ni Putu Ari; Wibawa, I Gede Jaya Satria; Wijaya, I Gede Bayu (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
This study aims to analyze employee job satisfaction in public service, and to analyze the implications of employee job satisfaction on public service in the Mataram City SAMSAT Office. The theory used in this research is satisfaction theory and motivation theory. The method used in this study is qualitative which is described in detail through observation and interviews with informants. This study uses two (2) types of data sources, namely primary data sources and secondary data sources. The data was obtained by means of interviews, observation, documentation, and methods of literature. The results of the study show that employee job satisfaction has not been fully fulfilled or is not satisfied, there are still some that have not been fulfilled, in employee job satisfaction there are 5 (five) indicators, namely; working conditions, wages, security, quality of supervision, and relationships with others. And employee job satisfaction has implications for public services in the Mataram City SAMSAT Office. This shows that the better the employee's job satisfaction, the better the employee's performance and vice versa, the less employee job satisfaction, the less employee performance job.